Thromboprophylaxis with argatroban in critically ill patients with sepsis: a review. Issue 5 (8th July 2022) - Bachler, Mirjam; Asmis, Lars M.; Koscielny, Jürgen; Lang, Thomas; Nowak, Hartmuth; Paulus, Patrick; Schewe, Jens-Christian; von Heymann, Christian; Fries, Dietmar
Abstract : During sepsis, an initial prothrombotic shift takes place, in which coagulatory acute-phase proteins are increased, while anticoagulatory factors and platelet count decrease. Further on, the fibrinolytic system becomes impaired, which contributes to disease severity. At a later stage in sepsis, coagulation factors may become depleted, and sepsis patients may shift into a hypo-coagulable state with an increased bleeding risk. During the pro-coagulatory shift, critically ill patients have an increased thrombosis risk that ranges from developing micro-thromboses that impair organ function to life-threatening thromboembolic events. Here, thrombin plays a key role in coagulation as well as in inflammation. For thromboprophylaxis, low molecular weight heparins (LMWH) and unfractionated heparins (UFHs) are recommended. Nevertheless, there are conditions such as heparin resistance or heparin-induced thrombocytopenia (HIT), wherein heparin becomes ineffective or even puts the patient at an increased prothrombotic risk. In these cases, argatroban, a direct thrombin inhibitor (DTI), might be a potential alternative anticoagulatory strategy. Yet, caution is advised with regard to dosing of argatroban especially in sepsis. Therefore, the starting dose of argatroban is recommended to be low and should be titrated to the targeted anticoagulation level and be closely monitored in the further course of treatment. The authors of this review recommend using DTIs such as argatroban as an alternative anticoagulant in critically ill patients suffering from sepsis or COVID-19 with suspected or confirmed HIT, HIT-like conditions, impaired fibrinolysis, in patients on extracorporeal circuits and patients with heparin resistance, when closely monitored.